Wacana Kekerasan Fisik dalam Komik Jurnalistik Footnotes in Gaza - Ridhani Agustama; Anang Hermawan (Jurnal Komunikasi)
Conflict between Israel and Palestine still become the hot issue that all media covering on it. But the information flow about the conflict is dominated by Western Media. The domination followed by Western Media’s effort to manipulate the information. For example, Western Media called Palestine as a dispute land; meanwhile if we look at the history it was the Israel colonized Palestine.